2017
DOI: 10.1080/03637751.2017.1322213
|View full text |Cite
|
Sign up to set email alerts
|

The fluency principle: Why foreign accent strength negatively biases language attitudes

Abstract: Two experiments tested the prediction that heavy foreign-accented speakers are evaluated more negatively than mild foreign-accented speakers because the former are perceived as more prototypical (i.e., representative) of their respective group and their speech disrupts listeners' processing fluency (i.e., is more difficult to process). Participants listened to a mild or heavy Punjabi-(Study 1) or Mandarin-accented (Study 2) speaker. Compared to the mildaccented speaker, the heavy-accented speaker in both studi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
93
2
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 92 publications
(105 citation statements)
references
References 59 publications
9
93
2
1
Order By: Relevance
“…The debriefing scores showed that affect was significantly lower for the foreign candidate than for the native and reported candidates, which was in line with Dragojevic and colleagues’ claim that processing fluency impacts affect (Dragojevic, 2019; Dragojevic & Giles, 2016; Dragojevic et al., 2017). This idea was reinforced by the fact that the easier the processing fluency (as reflected by the score for comprehensibility), the higher the score for social variables (affect, status and solidarity), as revealed by exploratory correlations across social and linguistic variables (not registered).…”
Section: Discussionsupporting
confidence: 81%
See 3 more Smart Citations
“…The debriefing scores showed that affect was significantly lower for the foreign candidate than for the native and reported candidates, which was in line with Dragojevic and colleagues’ claim that processing fluency impacts affect (Dragojevic, 2019; Dragojevic & Giles, 2016; Dragojevic et al., 2017). This idea was reinforced by the fact that the easier the processing fluency (as reflected by the score for comprehensibility), the higher the score for social variables (affect, status and solidarity), as revealed by exploratory correlations across social and linguistic variables (not registered).…”
Section: Discussionsupporting
confidence: 81%
“…However, although the variable foreignness stayed constant across the experiment, the variable processing fluency could vary across the experiment. Indeed, participants might first experience negative affect in response to difficulty in processing speech but might then adapt to a speaker's accent (Bradlow & Bent, 2008; Romero‐Rivas et al., 2015; but see, Floccia et al., 2009), which should lead to larger differences between the native candidate and the reported candidate than between the native candidate and the foreign candidate—in line with Dragojevic and colleagues’ (2016, 2017) reasoning about rewarding progress. One other possible case was that foreignness would be cancelled out when the foreign candidate's statements were reported by a native speaker.…”
Section: The Current Studymentioning
confidence: 80%
See 2 more Smart Citations
“…For instance, in social-psychological research on listeners' attitudes, speakers whom listeners perceived as hard to understand were downgraded in listeners' affective and attitudinal evaluations. Such speakers were ascribed negative emotions of annoyance and irritation and labelled less intelligent and successful (Dragojevic et al, 2017). Similarly, in a study focusing on online learning, when students evaluated an instructional video narrated by the instructor who was hard to understand, they downgraded the instructor in their evaluations, expressing negative attitudes towards online coursework and evaluating video content as more difficult, even though students' actual understanding of the video was not compromised (Sanchez & Khan, 2016).…”
Section: Comprehensibility: An Index Of Processing Fluencymentioning
confidence: 99%